Prevalence of glaucoma in Africa: A systematic review and Bayesian meta-analysis - Randy Asiamah; Samuel Kyei; Gideon Owusu; Patrick Evans Agyiri (PLoS ONE, 2025)
Purpose This study sought to establish the prevalence of glaucoma and the associated factors in Africa. Methods A systematic review of studies reporting the prevalence of glaucoma was performed using three electronic databases: PubMed, Scopus, and Web of Science. Data were extracted and study-specific estimates of the prevalence of glaucoma were combined using meta-analysis to obtain pooled proportions. Results A total of 9 studies that evaluated the prevalence of glaucoma in 29,606 individuals, comprising 14,487 males and 15,119 females were included in this study. The prevalence of glaucoma (unclassified glaucoma) in Africa was found to be 5.59% (95% Credible Interval (CrI) 4.32% to 7.74%). The prevalence of Primary Open-Angle Glaucoma (POAG), Primary Angle-Closure Glaucoma (PACG), and secondary glaucoma (SG) in Africa are 5.07% (95% (CrI) 3.51% to 8.52%), 0.98% (95% CrI 0.29% to 5.38%), and 2.19% (95% CrI 0.64% to 10.00%), respectively. The prevalence of glaucoma is highest in Southern Africa (6.47%, 95% CrI 3.10% to 12.10%) and lowest in East Africa (4.80%, 95% CrI 2.37% to 9.27%). The prevalence of POAG is highest in West Africa (6.48% 95% CrI 5.23% to 9.89%) and lowest in East Africa (3.23% 95% CrI 2.21% to 5.07%). Conclusion The prevalence rates of glaucoma and POAG are high, with geographical regional variations worthy of note. Continued efforts are necessary to implement population-based screening and public health education initiatives to foster early diagnosis and management.